Caracterização pedológica, uso da terra e modelagem da perda de solo em áreas de encosta do rebordo do planalto do RS - Miguel, Pablo (2010)
The river catchment Vacacaí Mirim is located where the water reservoir that supplies part of the water needs of the city of Santa Maria is located in a hillslope area of plateau border Southern Rio Grande. In these hillslope areas, due to the combination of strong relief is rolling to hilly common occurrence of soils with variable depth, with the predominance of shallow soils. The objectives were to conduct a study of current use and the evolution of land use and demarcation of areas of risk or potentially susceptible to loss of soil from the Universal Soil Loss Equation (USLE). The soil survey of semi-detailed, characterize the different soil classes occurring in the region. Through techniques of GIS maps were generated from soil, slope, Permanent Preservation Areas (PPAs), land suitability and land use evolution from 1987 to 2009. Map was made usability and identified areas of land use conflicts. According to the soil survey over 50% of the area consists of Entisols and over 50% of the area has less ability, being only suitable for the protection of fauna and flora. For the second study, the topographic factor (LS) was generated from the digital elevation model (DEM), the rainfall-runoff erosivity factor (R) data through normal rainfall, erodibility factor (K) the composition particle size of each class of soil, and cover-management and support practice factor (CP) through field observations and tabulated values. About 74% of the area has soil losses ranging 1 to 2 t ha-1.yr-1. Only 3% of the area has a soil loss of more than 20 t ha-1.yr-1, and of these 3%, 1% shows soil loss exceeding 50 t ha-1.yr-1. For assessing the potential loss of soil, the topographic factor (LS) was the most strongly determined the pace of erosion followed by the factor use and cover-management and support practice factor (CP) and soil erodibility factor (K). The aid of the image of computer application Google Earth is a very important tool in the evaluation of occupation and land use in the study area. The data gathered through this methodology for the estimation of factor use and cover-management and support practice factor (CP) are reliable and the researcher can make a conference field for a possible better definition of the classes of land use.